2015
DOI: 10.3389/fnagi.2014.00349
|View full text |Cite
|
Sign up to set email alerts
|

Emotion recognition in early Parkinson’s disease patients undergoing deep brain stimulation or dopaminergic therapy: a comparison to healthy participants

Abstract: Parkinson’s disease (PD) is traditionally regarded as a neurodegenerative movement disorder, however, nigrostriatal dopaminergic degeneration is also thought to disrupt non-motor loops connecting basal ganglia to areas in frontal cortex involved in cognition and emotion processing. PD patients are impaired on tests of emotion recognition, but it is difficult to disentangle this deficit from the more general cognitive dysfunction that frequently accompanies disease progression. Testing for emotion recognition d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(55 citation statements)
references
References 95 publications
4
49
2
Order By: Relevance
“…Although we are usually exposed to dynamic expressions in real‐life situations, very few studies investigating FER in PD used dynamic stimuli 30, 48, 49, 50. Because emotions are defined as transitory changes in several components of the organism, the dynamism of facial expressions plays a major role in emotion perception with a beneficial effect on FER accuracy 51.…”
Section: Discrepancies In Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although we are usually exposed to dynamic expressions in real‐life situations, very few studies investigating FER in PD used dynamic stimuli 30, 48, 49, 50. Because emotions are defined as transitory changes in several components of the organism, the dynamism of facial expressions plays a major role in emotion perception with a beneficial effect on FER accuracy 51.…”
Section: Discrepancies In Resultsmentioning
confidence: 99%
“…Although we are usually exposed to dynamic expressions in real-life situations, very few studies investigating FER in PD used dynamic stimuli. 30,[48][49][50] Because emotions are defined as transitory changes in several components of the organism, the dynamism of facial expressions plays a major role in emotion perception with a beneficial effect on FER accuracy. 51 Moreover, neuroimaging studies have highlighted differential neural activity for static versus dynamic facial emotions, with higher activation in response to dynamic stimuli in regions processing socioemotional information, motion and faces and that belong to the mirror neuron system: superior temporal sulcus (STS), visual area, fusiform gyrus, inferior frontal gyrus, amygdala, and orbitofrontal cortex (OFC).…”
Section: Stimulimentioning
confidence: 99%
See 1 more Smart Citation
“…However, the mood and behavioral changes after surgery remain somewhat unclear, as does the influence of STN DBS on the affective domain of Parkinson's disease (Castrioto, Lhommée, Moro, & Krack, 2014). While several studies comparing patients before and after surgery highlight a further deterioration in facial emotion and prosody recognition (Aiello et al, 2014;Biseul et al, 2005;Drapier et al, 2008;Dujardin, Blairy, Defebvre, Krystkowiak, et al, 2004b;Le Jeune et al, 2008;Peron, Biseul, et al, 2010a;Peron, Grandjean, et al, 2010b;Vicente et al, 2009), others found no such effect of STN DBS (Albuquerque et al, 2014;McIntosh et al, 2014). Likewise, while enhanced mood and emotional processing has been reported (Bruck, Wildgruber, Kreifelts, Krüger, & Wächter, 2011;Castner et al, 2007;Schneider et al, 2003), so has worsening (Schroeder et al, 2004;Serranova et al, 2011) or no change (Berney et al, 2007).…”
Section: Deep Brain Stimulation Of the Subthalamic Nucleus (Stn Dbs)mentioning
confidence: 99%
“…In AD mice, olfactory deficits also occurred before the clinical onset of cognitive deficits and coincided with AD pathology [5,6,7]. Olfactory dysfunction is prevalent in patients with AD and mild cognitive impairment [8], as the neuropathological abnormalities in both central and peripheral olfactory systems have been described in AD patients. Thus, olfactory dysfunction has been proposed as a potential biomarker for AD diagnosis [9,10].…”
Section: Introductionmentioning
confidence: 99%